Drop test of Seagate one inch micro hard disk drives : high speed camera - Chan, Ta Hoong. (2009)
In this project, a high speed camera is used to capture the video clips of the deflection of a Seagate one-inch micro hard disk drive upon a free drop of 1-inch in the first phase and proceeding to a rotary drop of 30 degrees, 50 degrees and 80 degrees. The video clips are analysed and measurements of the relative displacement of the hard disk drive slider from the disc platter are recorded. Thereafter, accelerometers are placed strategically to measure the shock caused by impact forces in the linear and rotary drop phases of the experiment. The results show that an increase in angle of rotary drop results in an increase in relative displacement of the hard disk drive. However, an increase in the angle of linear drop decreases the relative displacement of the hard disk drive. The peak relative displacements of the slider during the rotary drop phase are much higher than during the linear phase of the tests. This is further shown by the accelerometer readings. The accelerometers recorded higher shock pulses during the rotary drop phase than in the linear phase.